The EU budget as an opportunity in the crisis: The EU Commission proposal for a new financial framework and a reconstruction fund - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2020)
In response to the socio-economic consequences of the corona pandemic, the European Commission presented a comprehensive package of measures on 27 May 2020. It consists of two components. Firstly, the Commission's original proposal of May 2018 for the Multiannual Financial Framework (MFF) 2021-2027 is to be increased to exteuro1.8 trillion. Secondly, the Commission is proposing a temporary economic budget of exteuro750 billion under the title 'Next Generation EU'. This far-reaching package, which the Commission drew up in just a few weeks, can have the effect of fundamentally reshaping European budgetary policy and redistributing competences and responsibilities between the EU and the member states. The result could be a significant deepening of European integration.
Keywords: 320